Penghentian Penyidikan Kasus Kecelakaan Lalu Lintas di Polres Boyolali - Elsa Ananda Putri; Suciyani (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
Traffic accidents are caused by human error and negligence.  Traffic accidents that can harm property or the lives of others caused by human factors, vehicles, roads and the environment as well as weather factors.  Traffic accidents that result in the death of the victim must be subject to legal proceedings according to applicable law starting from an investigation by the police, prosecution by the prosecutor's office and the court by the court to obtain a decision, but in practice investigators can stop the legal process.  This research is classified as a qualitative research, namely by processing primary data obtained by the parties concerned with cases of traffic accidents that cause the loss of other people's lives, as well as data that are considered important which are generated by direct interviews at the research location.  The conclusion in this study is that the process of stopping the investigation carried out by the police at the Boyolali Police can reflect a sense of justice between the suspect's family and the victim's family which was carried out with family deliberation so that they were given the opportunity to express their opinions and desire to find good solutions to the problems faced by both parties.  party.  Islam places peace/islah as an alternative in resolving criminal cases, as long as the case has not yet reached the hands of the judge.  This principle can be realized by resolving criminal cases with peace at the level of investigation.